Volatility Spillovers between Interest Rates and Equity Markets of Developed Economies - Wilson Donzwa; Rangan Gupta; Mark E. Wohar (Journal of Central Banking Theory and Practice, 2019)
This study employs the recently developed Lagrange multiplier-based causality-in-variance test by Hafner and Herwartz (2006), to determine the volatility spillovers between interest rates and stock returns for the US, the euro area, the UK, and Japan. The investigation pays careful attention to volatility transmissions between stock returns and interest rates before and after these economies reached the Zero Lower Bound (ZLB), which is permitted via the use of Shadow Short Rates (SSR), used as a proxy for monetary policy decisions. The results based on daily data imply that while bi-directional causality is observed, the volatility spillover from interest rates to stock markets are more prominent for the full-sample, as well as the sub-samples covering the pre- and during-ZLB periods.
Keywords: C32; C58; E43; G1; 330; Interest Rates; Stock Markets; Volatility Spillover.